Hubungan Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) Keluarga terhadap Kejadian Infeksi Saluran Pernapasan Akut (ISPA) pada Balita di Puskesmas Mandai Kabupaten Maros - Aprilia, Salsabila Tirta; Rijal, Syamsu; Wiriansya, Edward Pandu; Vitayani, Sri; Nasruddin, Hermiaty (Wal'afiat Hospital Journal, 2024)
This study aims to explore the relationship between the implementation of clean and healthy living behaviors (PHBS) in the family with the incidence of Acute Respiratory Infections (ARI) in toddlers at Puskesmas Mandai, Maros Regency. Using a quantitative approach with a correlation analytic method, this study involved 58 toddlers aged 0-5 years who were diagnosed with ARI. The results showed that 58.6% of respondents were male, with the largest age group 0-12 months (25.9%). 74.1% of the toddlers were not exclusively breastfed, and 80.9% were underweight. In addition, 75.7% of respondents did not have the habit of washing hands with soap, and 94.8% lived in an environment with active smokers. Bivariate analysis showed a significant association between the PHBS variables and the incidence of ARI, with P values less than 0.05 for all variables. These results suggest that the implementation of exclusive breastfeeding, routine weighing of toddlers, hand washing with soap, and not smoking in the house play an important role in reducing the incidence of ARI. Therefore, health centers are advised to increase the socialization of PHBS and education about the dangers of smoking, as well as encourage the community to apply clean living behavior in everyday life. This study is expected to be the basis for improving health programs at Puskesmas Mandai and increasing public awareness about the importance of PHBS in preventing ARI.